The Tortricidae (Lepidoptera) of Bhutan - Groenen, Frans; Wangdi, Karma (Zootaxa, 2019)
Twenty-five species of Tortricidae from Bhutan are discussed, 14 of which are recorded for the first time: Acleris perfundana Kuznetsov, 1962, Archips limatus Razowski, 1977, Chirapsina expleta (Meyrick, 1923), Clepsis humana (Meyrick, 1912), Adoxophyes privatana (Walker, 1863), Lumaria probolias (Meyrick, 1907), Meridemis bathymorpha Diakonoff, 1976, Isodemis illiberalis Meyrick, 1918, Lobesia ambigua Diakonoff, 1954, Metendothenia ordospina Jirasuttayaporn & Pinkeaw, 2018, Gibberifera glaciata (Meyrick, 1907), Crocidosema plebejana Zeller, 1847, Lepteucosma charassuncus Razowski, 2006, and Microsarotis bicincta Diakonoff, 1976. Females of Chirapsina expleta and Epiblema charadrias Diakonoff, 1977 are described and illustrated for the first time. Nine new species are described: Eupoecilia jakarana, sp. nov., E. gedui, sp. nov., Lumaria phuntschona, sp. nov., Borneogena trashiyana, sp. nov., Bactra cophinana, sp. nov., Penthostola subnigrantis, sp. nov., M. brunnofasciana, sp. nov., Peridaedala nigrifasciana, sp. nov., and Epiblema albulusana, sp. nov. Adults and their genitalia are illustrated.